Cytotoxic Effects of Cinnamon Powder and Lemongrass Oil-Enriched Roselle Tea on T47D Breast Cancer Cells - Aisyah, Sabila; Cahyono, Edy; WH, Nugrahaningsih; Alighiri, Dante; Alauhdin, Mohammad; Zaky, Adrian Maulana; Handayani, Tri; Permatasari, Bella (Indonesian Journal of Cancer Chemoprevention, 2024)
Breast cancer is the most prevalent cancer among women and is the leading cause of cancer-related mortality worldwide. This underlines the importance of preventive strategies to reduce the risk. Harnessing natural products like tea could be an alternative preventive strategy. In this study, the chemopreventive potential of roselle flower tea (Hibiscus sabdariffa L.) enriched with cinnamon oil (Cinnamomum burmannii) and lemongrass (Cymbopogon citratus) was evaluated. The tea was formulated using a stirred boiler tank and tested for its cytotoxicity against T47D cells using the MTT method. The cytotoxicity test showed that with the addition of cinnamon oil and lemongrass, roselle tea had more significant cytotoxic activity against T47D cancer cells than pristine roselle tea. Adding 5 g of cinnamon and lemongrass oil vapor for 15 seconds into the tea showed the highest cytotoxicity, with an IC50 of 730 μg/mL. This value is almost three times higher than without adding cinnamon oil and lemongrass. In conclusion, adding cinnamon oil and lemongrass to the roselle tea formulation can increase cytotoxic activity against T47D cancer cells, indicating its potential as a natural anti-cancer agent.Keywords: Chemopreventive, Cinnamon, Lemongrass, Roselle Tea, T47D Cells.